Lillianites and andorites: new life for the oldest homologous series of sulfosalts. (April 2014) - Makovicky, E.; Topa, D.
Abstract: The current state of the lillianite homologous series is presented, with its two branches − the lillianite branch of the predominantly Pb-Bi-Ag sulfosalts and the andorite branch of predominantly Pb-Sb-Ag sulfosalts. Both the natural and synthetic members are discussed, especially from the structural and compositional point of view and the related, chemically distinct and structurally more complicated members of the series are described. A number of new published, or hitherto unpublished observations is given, together with fairly exhaustive tables of data. Relationships between the complex structures of different 'andorite' species and principal structural features of 'oversubstituted' As-Sb and Bi-Sb species are discussed. Contrary to many studies of this subject, synthetic phases form an integral part of the paper. It is concluded that research in this long-known homologous series still supplies new interesting phases, especially in the fields of synthetic products and in its andorite branch.